“El Libro de Alexandre: el clérigo al servicio del rey” - Arizaleta, Amaia (Troianalexandrina, 2008)
Abstract This article puts forward a number of examples that may perhaps contribute to confirm the idea that the Libro de Alexandre came from Castilian-Leonese palace circles in the first third of the thirteenth century. This study also suggests that it may have been one of the forms adopted by the monarch's moral and political education, functioning in a manner similar to the Chronica regum Castellae, the Chronicon mundi or even the Historia de rebus Hispaniae, for example. Whilst advancing the theory that historiographical fiction and poetic fiction had many features in common in the context of court reception, an attempt is thus made to demonstrate that the clerical men of letters put their art at their sovereign's disposal.